POWER FLOW OPTIMIZATION FOR GRID CONNECTED INVERTER USING EVOLUTIONARY ALGORITHM AND ADDITIONAL CONTROL LOOP - Carniato, L. A.; Godoy, R. B.; Pinto, J. O. P.; Canesin, C. A. [UNESP]; Garcia, R. C.; IEEE (Ieee, 2011)
In this work it is proposed to validate an evolutionary tuning algorithm in plants composed by a grid connected inverter. The optimization aims the tuning of the slopes of P-omega and Q-V curves so that the system is stable, damped and minimum settling time. Simulation and experimental results are presented to prove the feasibility of the proposed approach. However, experimental results demonstrate a compromising effect of grid frequency oscillations in the active power transferring. In addition, it was proposed an additional loop to compensate this effect ensuring a constant active power flow.
Keywords: Inverters; modeling; optimization; grid-connected operation; power oscillations minimization